Impact of coronary intensive care unit in treatment of myocardial infarction - Todo, Marcia Cristina [UNESP]; Bergamasco, Carolina Marabesi [UNESP]; Azevedo, Paula Schmidt [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Inoue, Roberto Minoru Tanni [UNESP]; Okoshi, Marina Politi [UNESP]; De Paiva, Sergio Rupp [UNESP]; Zornoff, Leonardo Mamede [UNESP]; Polegato, Bertha Furlan [UNESP] (FapUNIFESP (SciELO), 2017)
Introduction: The mortality rate attributed to ST-segment elevation myocardial infarction (STEMI) has decreased in the world. However, this disease is still responsible for high costs for health systems. Several factors could decrease mortality in these patients, including implementation of cardiac intensive care units (CICU). The aim of this study was to evaluate the effect of CICU implementation on prescribed recommended treatments and mortality 30 days after STEMI. Method: We performed a retrospective study with patients admitted to CICU between 2005 and 2006 (after group) and between 2000 and 2002, before CICU implementation (before group). Results: The after group had 101 patients, while the before group had 143 patients. There were no differences in general characteristics between groups. We observed an increase in angiotensin-converting enzyme inhibitors, clopidogrel and statin prescriptions after CICU implementation. We did not find differences regarding number of patients submitted to reperfusion therapy; however, there was an increase in primary percutaneous angioplasty compared with thrombolytic therapy in the after group. There was no difference in 30-day mortality (before: 10.5%; after: 8.9%; p=0.850), but prescription of recommended treatments was high in both groups. Prescription of angiotensin-converting enzyme inhibitors and beta-blocker decreased mortality risk by 4.4 and 4.9 times, respectively. Conclusion: CICU implementation did not reduce mortality after 30 days in patients with STEMI; however, it increased the prescription of standard treatment for these patients.
Keywords: Adrenergic Antagonists.; Angiotensin-Converting Enzyme Inhibitors; Mortality